Punishing The Bankruptcy Fraudsters: What Can Indonesia Learn from United States of America? - Robert, Robert; Agustina, Rosa; Nasution, Bismar (Faculty of Law, Universitas Jenderal Soedirman, 2020)
Bankruptcy is a system that was created to provide financially distressed debtors relief from their debts while providing the creditors with a fair portion of the debtors’ assets. Unfortunately, certain parties might attempt to beat the system unfairly. The goals of this study are to compare Title 18 United States Code with Indonesia’s legal system regarding bankruptcy fraud and how the Indonesian bankruptcy law ought to be in regulating bankruptcy fraud. This research is qualitative, using a black letter method and legal comparative approach. The result of this study shows that Indonesian bankruptcy law does not regulate provisions regarding bankruptcy fraud as comprehensive as Title 18 United States Code. It is suggested that the Indonesian government amends the bankruptcy law, therefore the public’s confidence in the bankruptcy system can be preserved while providing a deterrence effect for the participants who might exploit the bankruptcy system for their advantages. Keywords: bankruptcy; bankruptcy crime; fraud; white collar crime